Pengembangan Media Pembelajaran Video Pada Patient Safety Virtual Education - Suci Noor Hayati; Eva Supriatin; Tri Antika (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
The advancement of educational technology necessitates the use of technologically qualified learning media. Video-based learning is one of the learning tools that can help to create an engaging and enjoyable learning environment. This study aimed to develop a video learning media product for patient safety and virtual educational learning. The research design adapts the ADDIE development paradigm, which stands for Analysis, Design, Development, and Implementation, to apply the Research and Development technique. Material and media expert validation was carried out during the development stage by testing the instrument's usability. The trial was carried out by 124 students to see how they reacted as users. According to media and material specialists, video learning medium is valid and appropriate for use in virtual patient safety courses. The average value of 3.79 for user response to video learning medium indicates that there is a high level of interest in learning through the use of video. User response to video learning media by looking at learning interest with an average value of 3.79 means that there is a good interest in learning by using video media to be used in patient safety learning in virtual education. The use of engaging learning media such as films can boost student interest in learning and help them attain skills, which is especially important in virtual patient safety training. It is envisaged that the development can be completed at the evaluation stage, but it will need to be upgraded in order to present an actual simulation that students can understand.